Optimalisasi Pemanfaatan Bantaran Sungai Anak Brantas dalam Upaya Peningkatan Ketahanan Pangan di Sidoarjo - Anif Muchlashin; Edi Martono; Subejo Subejo (IAIN Salatiga, 2019)
The purpose of this research was (1) to describe the optimization of river bank usage in achieving food security by Eksis Forever Youth Organization; (2) to analyse obstacles which were faced by Eksis Forever Youth Organization in optimizing river bank; (3) to examine its implication to food security in Desa Keboan Anom, Kecamatan Gedangan, Kabupaten Sidoarjo.This study used descriptive qualitative. The data were compiled through observation, interview, documentation and focus group discussion (FGD). The findings show that (1) Eksis Forever Youth Organization had succeeded in manufacturing the nutrition garden by utilizing river bank to raise the economical of some families; (2) the obstacles came from the intern and the extern; (3) the implication of findings in this research was in environment, economy and social as well as the improvement of human resource especially young generation.